Pulmonary artery intimal sarcoma mimicking pulmonary thromboembolism: A case report. Issue 6 (12th February 2021) - Li, Ying-Chun; Li, Le-Yao; Tong, Hai-Chao; Xu, Hong-Tao; Ma, Shuang; Yang, Lian-He; Zhang, Wan-Lin; Sotolongo, Gina; Wang, Endi
Abstract: Rationale: Pulmonary artery intimal sarcoma is a rare tumor with exceptionally high mortality and easily misdiagnosed as pulmonary thromboembolism pulmonary thromboembolism (PTE) due to the nonspecific clinical presentation and symptom. Misdiagnosis or untimely diagnosis makes the disease progress to an advanced stage and eventually leads to a poor prognosis. Patient concerns: A 37-year-old Chinese female presented with chest tightness and dyspnea for 3 months. Echocardiography and chest computed tomography revealed an intraluminal obstruction of the pulmonary arteries. Tests of serum tumor makers showed slight elevation for carbohydrate antigen-125, and α-fetoprotein. PTE was suspected according to the radiological and laboratory findings. Diagnosis: Microscopic findings of the presumed thrombus showed prominent myxoid and edematous background with atypical spindled cells and curvilinear vascularity. Immunohistochemical staining demonstrated that the atypical spindled cells were positive for vimentin but negative for CK, S100, SMA, desmin, CD68, STAT6, CD34, β-catenin, ALK-p80, p53, and MDM2. According to the radiological and pathological findings, the diagnosis of fibrosarcoma of pulmonary artery was made. Interventions: The patient underwent surgical resection and the mass was excised as completely as possible. Outcome: Follow-up information showed no evidence of recurrence or metastasis after 3 months postresection. Lessons: Because of the low incidence rate, nonspecific clinical symptoms, and radiological findings, primary fibrosarcoma of the pulmonary artery is commonly misdiagnosed as PTE. Pathological examination is necessary to confirm the diagnosis.